2006
DOI: 10.1021/cb6003228
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Bioorthogonal Reactions with Azides

Abstract: Detection of metabolites and post-translational modifications can be achieved using the azide as a bioorthogonal chemical reporter. Once introduced into target biomolecules, either metabolically or through chemical modification, the azide can be tagged with probes using one of three highly selective reactions: the Staudinger ligation, the Cu(I)-catalyzed azide-alkyne cycloaddition, or the strain-promoted [3 + 2] cycloaddition. Here, we compared these chemistries in the context of various biological application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
621
0
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 678 publications
(659 citation statements)
references
References 33 publications
(65 reference statements)
13
621
0
13
Order By: Relevance
“…38, ‡ Interestingly, the efficiency of 30 capture by [3 + 2] cycloaddition (or 'click' chemistry) appears to be superior to that of capture with the Staudinger-Bertozzi reagent under the conditions used, an observation that corroborates a previous comparative study of bioorthogonal ligation approaches. 5 [3 + 2] capture of azide tagged protein 35 with 14 is also superior to that of alkyne tagged protein with 13 under identical conditions, an observation noted previously by Cravatt and co-workers. 39 This is likely due to the enhancement in rate in the presence of a large excess of activated alkyne in the case of capture using reagent 14; in the 40 case of capture with 13, the rate is presumably limited by the relatively lower concentration of activated alkynyl-protein.…”
mentioning
confidence: 61%
“…38, ‡ Interestingly, the efficiency of 30 capture by [3 + 2] cycloaddition (or 'click' chemistry) appears to be superior to that of capture with the Staudinger-Bertozzi reagent under the conditions used, an observation that corroborates a previous comparative study of bioorthogonal ligation approaches. 5 [3 + 2] capture of azide tagged protein 35 with 14 is also superior to that of alkyne tagged protein with 13 under identical conditions, an observation noted previously by Cravatt and co-workers. 39 This is likely due to the enhancement in rate in the presence of a large excess of activated alkyne in the case of capture using reagent 14; in the 40 case of capture with 13, the rate is presumably limited by the relatively lower concentration of activated alkynyl-protein.…”
mentioning
confidence: 61%
“…We previously explored the use of ring strain, demonstrating that cyclooctynes, the smallest of the stable cycloalkynes, can achieve bioorthogonal labeling of azides (14). Although the sensitivity of this strain-promoted cycloaddition was no better than that of the Staudinger ligation, the cyclooctyne probes demonstrated no cellular toxicity and offered a platform for further reaction development using the principles of physical organic chemistry (15).…”
Section: Resultsmentioning
confidence: 99%
“…In its original format, the SPAAC reaction displayed similar, relatively slow, kinetics to the Staudinger ligation (Fig. 4a) 67 . To improve the rate, both difluorinated cyclooctynes 92 (DIFO) and dibenzocylooctynes 93 were independently reported allowing the visualisation of dynamic processes.…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 91%
“…More recently, Serwa et al 66 reported a phosphite-Staudinger reaction with a stalled intermediate phosphoramidate. In addition to negating the problem of possible phosphine oxidation 67 , this 'traceless' reaction valuably allows installation of phosphate mimics 66 .…”
Section: Modifications At Uaasmentioning
confidence: 99%
See 1 more Smart Citation